Antroponym translation in children’s literature – early 20th and 21st centuries - Fornalczyk, Anna (Kalbotyra, 2007)
The focus of my paper lies within a new field of research which is situated at the intersection of two academic disciplines: translation studies and children’s literature, the so called children’s literature translation studies (CLTS). [...]